Hybrid Half- and Full-Duplex Communications Under Correlated Lognormal Shadowing - Lima, Carlos H. M. de [UNESP]; Alves, Hirley; Nardelli, Pedro H. J.; Latva-aho, Matti; IEEE (Ieee, 2015)
This paper investigates a hybrid network configuration in which full-duplex base stations serve half-duplex users on both Uplink and Downlink simultaneously. Users are modeled as a homogeneous Poisson point process while the channel is modeled as a composite fading with correlated Log-normal shadowing and Nakagami-m fading. We characterize the signal-to-interference-ratio at an user of interest, and then evaluate how the network performs in terms of outage probability. We account for the cross-correlation between the user of interest and a random co-site interferer within range. Thus, we provide a valuable insight on on how the hybrid network performs under the assumption of correlated shadowing. We show that when the aforesaid correlation is low, the user of interest can achieve higher data rate at expense of high outage; however, if the distance to the serving base station is short and the cross correlation is high, a satisfactory data rate can be sustained at low outage.